Programmable immunoprobiotics orchestrate antitumor immune response with Pin1 inhibition for pancreatic cancer treatment - Sichen Yuan; Xicheng Yang; Alexa M. Bremmer; Yixin Wang; Sherry Li; Yu Chen; Yawen You; Quanyin Hu (Proceedings of the National Academy of Sciences, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is a highly aggressive cancer with limited treatment options due to its desmoplastic and immunosuppressive tumor microenvironment (TME), which impedes drug delivery and limits T cell infiltration. Immune checkpoint blockade (ICB) has shown poor efficacy in PDAC, partly due to the desmoplastic stroma and low immunogenicity. Peptidyl-prolyl cis/trans isomerase NIMA-interacting 1 (Pin1) promotes both fibrosis and immune evasion, making it a compelling target for TME remodeling. Here, we develop a dual-action, programmable immunoprobiotic delivery system (EcN@Nbs-NP@API-1) that combines Pin1 inhibition with PD-L1 blockade to enhance immunotherapy. This system uses Escherichia coli Nissle 1917 (EcN) to selectively deliver nanoparticles encapsulating the Pin1 inhibitor API-1 to PDAC, enabling sustained release to degrade the fibrotic stroma and upregulate PD-L1 on tumor cells, promoting immune infiltration. Engineered EcN also produces anti-PD-L1 nanobodies in situ, synergizing with API-1 to boost CD8 + T cell–mediated immunity. In orthotopic PDAC mouse models, this strategy remodels the TME, enhances immune cell infiltration, and improves antitumor response while minimizing systemic toxicity. Moreover, it shows efficacy in other ECM-rich tumors, such as triple-negative breast cancer, highlighting its broader potential. This work presents a promising platform to overcome immunotherapy resistance in solid tumors.